Motivasi Kelompok Kesenian Sintren Sokoaji untuk Melaksanakan Pertunjukkan Keliling di Kabupaten Pekalongan - Indah Ningrum; Joko Wiyoso (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to describe the driving factors behind the Sintren Sanggar Sokoaji arts group's touring performances in Pekalongan Regency. The study employed a qualitative approach with descriptive methods. The research location was at Sanggar Sokoaji, Pekalongan Regency, and involved 10 informants: the studio leader, dancers, musicians, shamans, and members of the group. Data were collected through observation, interviews, and documentation. Data validity was achieved through source and technical triangulation. Data analysis employed the interactive model of Miles, Huberman, and Saldaña, encompassing data reduction, data presentation, and conclusion drawing. The results indicate that the Sintren Sanggar Sokoaji arts group's touring performances are driven by four main factors: economic, cultural preservation, social, and efforts to maintain the group's existence. Economic factors relate to efforts to generate income to support studio operations and meet the needs of members. Cultural preservation factors arise from the group's desire to maintain the sustainability of Sintren art as a regional cultural heritage. Social factors relate to efforts to interact with the community while providing entertainment. Efforts to maintain the group's existence are realized through activities to introduce and maintain the Sanggar Sokoaji presence amidst the development of modern entertainment. Research findings indicate that cultural preservation is the most dominant factor driving the Sanggar Sokoaji Sintren arts group to tour in Pekalongan Regency.